Influence of 25-hydroxy-vitamin D insufficiency on maximal aerobic power in elite indoor athletes: A cross-sectional study - Most, A.; Dörr, O.; Nef, H.; Hamm, C.; Bauer T.; Bauer, P. (Sports Medicine - Open, 2021)
Background The impact of vitamin D on musculoskeletal health is well-established, although its influence on physical performance is unclear. Therefore, we conducted this study to evaluate the impact of 25-hydroxy-vitamin D (25-OH vitamin D) concentrations with maximal aerobic power of professional indoor athletes.